Calculating geothermal heat flux in Antarctica and evaluating its impact on the cryosphere - Miller, Anne (2018)
Geothermal heat flux (GHF) is an essential boundary condition that has a dynamic influence over ice sheet mass balance. Difficulties associated with obtaining GHF measurements in ice covered regions mean that GHF in Antarctica is not well understood. A combination of seismic, magnetic, and rock property analysis methods have given quantities for Antarctic GHF. Via manipulation of these past measurements this review finds the average GHF value across Antarctica to be ~70 mW/m2. This GHF value equates to 7 mm/year of ice melt directly from GHF. Integrated across the entire ice sheet this melt rate is almost negligible at <1% of the total ice melt in Antarctica. Where GHF is of greatest importance is the effect it has on basal hydrology. Meltwater generated from GHF beneath the ice sheet has the potential to alter ice flow properties. Consequences of meltwater include changing ice flow velocity, and the formation of drainage channels and lakes. These factors have a huge influence on ice sheet mass balance. Consideration of these effects is essential to create accurate ice mass balance models and understand the role of GHF in the Antarctic cryosphere. Moving forward it is imperative GHF is accurately quantified and appropriately interpreted in a subglacial hydrological system.